Pengembangan Kognitif Anak Dalam Perspektif Al-Qur’an Dan Psikologi Pendidikan - Dzawata Afnan Habib El Hakiem; Sultanah Hasan Al Juhi; Izrail Arsy Sulthan Swandana (Program Studi Psikologi Islam, 2025)
This article explores the integration between Qur’anic epistemology and educational psychology in developing children’s cognitive potential. Using a qualitative library research method, the study analyzes Qur’anic verses, classical Islamic thought (al-Ghazālī, Ibn Sīnā, Ibn Khaldūn), and contemporary psychological theories (Piaget, Vygotsky, and Bruner). The findings reveal that while psychology explains the structure of thinking, Islam explains the purpose of thinking. The Qur’an views intellect (‘aql) as a divine trust that leads humans toward ma‘rifatullāh (the knowledge of God) through reflection (tafakkur) and contemplation (tadabbur). The synthesis produces a Qur’anic Cognitive Development Framework (QCDF) that consists of three stages: (1) the activation of innate potential (fitrah), (2) reflective exploration through experience, and (3) rational-spiritual maturity. Practically, the integration encourages teachers to apply Qur’anic reflection-based learning and design holistic assessments that include spiritual reasoning. The study concludes that true cognitive education in Islam aims not only to produce intelligent minds but also enlightened hearts that think within the guidance of divine revelation.